Surgical treatment for post-infarction papillary muscle rupture: a multicentre study. (31st October 2021) - Massimi, Giulio; Ronco, Daniele; De Bonis, Michele; Kowalewski, Mariusz; Formica, Francesco; Russo, Claudio Francesco; Sponga, Sandro; Vendramin, Igor; Falcetta, Giosuè; Fischlein, Theodor; Troise, Giovanni; Trumello, Cinzia; et al.
Abstract:  : OBJECTIVES: Papillary muscle rupture (PMR) is a rare but potentially fatal complication of acute myocardial infarction. The aim of this study was to analyse the patient characteristics and early outcomes of the surgical management of post-infarction PMR from an international multicentre registry. METHODS: Patients underwent surgery for post-infarction PMR between 2001 through 2019 were retrieved from database of the CAUTION study . The primary end point was in-hospital mortality. RESULTS: A total of 214 patients were included with a mean age of 66.9 (standard deviation: 10.5) years. The posteromedial papillary muscle was the most frequent rupture location (71.9%); the rupture was complete in 67.3% of patients. Mitral valve replacement was performed in 82.7% of cases. One hundred twenty-two patients (57%) had concomitant coronary artery bypass grafting. In-hospital mortality was 24.8%. Temporal trends revealed no apparent improvement in in-hospital mortality during the study period. Multivariable analysis showed that preoperative chronic kidney disfunction [odds ratio (OR): 2.62, 95% confidence interval (CI): 1.07–6.45, P  =   0.036], cardiac arrest (OR: 3.99, 95% CI: 1.02–15.61, P  =   0.046) and cardiopulmonary bypass duration (OR: 1.01, 95% CI: 1.00–1.02, P  =   0.04) were independently associated with an increased risk of in-hospital death, whereas concomitant coronary artery bypass grafting was identified as an independent predictor of early survival (OR: 0.38, 95% CI: 0.16–0.92, P  =   0.031). CONCLUSIONS: Surgical treatment for post-infarction PMR carries a high in-hospital mortality rate, which did not improve during the study period. Because concomitant coronary artery bypass grafting confers a survival benefit, this additional procedure should be performed, whenever possible, in an attempt to improve the outcome. Clinical trial registration: clinicaltrials.gov: NCT03848429. Abstract : Papillary muscle rupture (PMR) is an infrequent but life-threatening mechanical complication (MC) of acute myocardial infarction (AMI) [1].